(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Informed consent is essential in ensuring the autonomy of participants in clinical research. However, informed consent documents are often complex and difficult to understand, and do not incorporate the patients’ perspective. The informed consent process has become more focused on acquiring the participant’s signature on the informed consent form, rather than being a contract that ensures the patient’s autonomy through clear and complete information about all relevant aspects of a trial. The i-CONSENT project aims to improve the information that potential participants receive when deciding whether or not to join a clinical trial through the development of a set of guidelines for the informed consent process. Involving potential participants during the preparation of the informed consent and its associated materials can be a key factor.